Effect of Fluconazole on the Fertility of Male Rabbits - El-Medany, Azza H.; Hagar, Hanan H. (Arzneimittelforschung, 2002)
Azole derivatives are currently available for oral treatment of systemic mycosis. They act by affecting the membrane permeability of sensitive cells through alterations of the biosynthesis of lipids, especially sterols, in the fungal cell. The present work was conducted to investigate the possible side effects of a newer azole derivative, fluconazole (CAS 86386-73-4), on fertility in sexually mature male rabbits and to elucidate the underlying mechanisms of this effect.Oral administration of fluconazole (50 mg/kg body weight in distilled water) daily for one month to sexually mature male rabbits induced a significant decrease in serum testosterone, semen volume, count and percentage of motile sperms. A significant increase in serum prolactin, follicle stimulating hormone and luteinizing hormone was observed. On the other hand, a non-significant alteration in percentage of abnormal sperm forms was noticed. After one month drug cessation, hormonal profile, sperm counts and percentage of motile sperms were still significantly distorted, and the whole profile reversed back towards normal only after the second month of drug cessation.Testicular biopsies showed no histopa-thological changes. From the above mentioned results, it can be concluded that fluconazole induced functional and reversible alterations in male fertility. Though the primary brunt of action appears to be operating on testicular level, however, a secondary direct interplay on higher central controls seems obviously contributing. Caution is advised when using azole derivatives in male patients, especially those on prolonged therapy.
Keywords: Antifungal drugs; CAS 86386-73-4; Fluconazole; Follicle-stimulating hormone; Luteinizing hormone; Male fertility; Prolactin; Testosterone